(untitled) (Fiep Bulletin - online, 2014)
The objective of the study was to investigate two methods of training with the objective to develop the power of lower and upper members in a combat modality where the muscular power is essential, being necessary the use of specific training that can propitiate an increase in the performance of the practitioners of this modality. For the accomplishment of this study, two groups with 06 individuals had been formed each, being one of the feminine sex in each group. The two groups had been submitted the tests of power of superior and lower members (JOHNSON and NELSON, 1979), establishing average for the two groups. In the sequence these groups had been subjected the eight weeks of training, being the group submitted to the pliometric training and group B to the resistance training and force with the weight of the proper body. To the ending of the eight weeks, the groups had been submitted to the same tests, establishing new averages and comparing the results, where he was evidenced the superiority of the pliometric training, that besides in such a way increasing the power of how much lower the upper members, still that one presented its results in a upper speed that other training could present. It was observed estatisticamente that it did not have significant difference between the two methods.